(untitled) (Dialogos, 2016)
Resenha do livro: KOSELLECK, Reinhart; MEIER, Christian; GÜNTHER, Horst; ENGELS, Odilo. O conceito de História. Trad. René E. Gertz. Belo Horizonte: Autêntica, 2013. 230 p.